2023
DOI: 10.1523/jneurosci.0587-23.2023
|View full text |Cite
|
Sign up to set email alerts
|

Parabrachial Nucleus Activity in Nociception and Pain in Awake Mice

Abstract: The parabrachial nuclear complex (PBN) is a nexus for aversion, and for the sensory and affective components of pain perception. We have previously shown that, during chronic pain, PBN neurons in anesthetized rodents have amplified activity. We report a method to record from PBN neurons of behaving, head-restrained mice, while applying reproducible noxious stimuli. We find that both spontaneous and evoked activity are higher in awake animals, compared to urethane anesthetized mice. Fiber photometry of calcium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that the in vivo fiber photometry system could monitor the deep brain regions such as the ACC and prefrontal cortex, which comprise the pain matrix. [12][13][14][15][16] The results of these studies suggested that combination experiments of in vivo fiber photometry and behavior tests enable us to understand the interaction between changes of neuronal activities in pain matrix which contribute to affective component of pain and pain modulation, pain induced anxiety, or cognition of pain. On the other hand, we also monitored changes of calcium responses in the S1 cortex before and after administration of CFA, resulting that averaged amplitude of calcium responses in S1 were significantly increased 3 or 7 d after injection of CFA, in present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that the in vivo fiber photometry system could monitor the deep brain regions such as the ACC and prefrontal cortex, which comprise the pain matrix. [12][13][14][15][16] The results of these studies suggested that combination experiments of in vivo fiber photometry and behavior tests enable us to understand the interaction between changes of neuronal activities in pain matrix which contribute to affective component of pain and pain modulation, pain induced anxiety, or cognition of pain. On the other hand, we also monitored changes of calcium responses in the S1 cortex before and after administration of CFA, resulting that averaged amplitude of calcium responses in S1 were significantly increased 3 or 7 d after injection of CFA, in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, to identify the involvement of neuronal activities in the pain matrix in the development of chronic pain symptoms such as the sensory and affective components of pain, combined experiment with the behavior tests and in vivo calcium imaging using fiber photometry was applied. [12][13][14][15][16] The effects of drugs such as dexmedetomidine and duloxetine into ACC in chronic or inflammatory pain model mice with expressed GCaMP were measured using this combined experiment. As the results, administration of abovementioned drugs reduced the calcium responses of glutamatergic neurons in ACC and showed the anti-anxiety like behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation